Analysis of the Use of Thematic Learning Video Media on the Learning Interest of Fifth-Grade Students at SDN Serang 10 - Mudrikah Mudrikah; Trian Pamungkas Alamsyah; Sigit Setiawan; Ana Nurhasanah (Universitas Pendidikan Indonesia Kampus Serang, 2022)
This study discusses the use of thematic learning video media on the learning interest of fifth-grade students at SDN Serang 10. This research focuses on three things: planning in the use of thematic learning videos, implementation of thematic learning videos for fifth grade, and students' learning interests after using thematic learning video media. The method used was descriptive qualitative with data collection techniques of interview, observation, questionnaire, and documentation. This research was carried out at SDN Serang 10 from April to June 2022, with 27 students in the fifth grade as the research subjects. This study’s results revealed that the planning of using instructional video media was good. Educators made their learning video media by improving their abilities, with three stages: pre-production, production, and post-production. Then, implementing the use of learning video media was considered good and effective as a solution to the challenges of educators creating effective learning and realizing students' learning interests. Even though there were obstacles, educators tried to overcome them and find solutions so that learning could be carried out optimally. The instructional video media use also showed that students' learning interest was very good, assessed from the student learning interest questionnaire results with a score of 80.98%. Besides, interviews and observations uncovered a sense of pleasure, interest, attention, and involvement in learning activities. This implementation can be good practice for using media for elementary school teachers